2016
DOI: 10.1155/2016/5246217
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mullerian Hormone:Above and Beyond Conventional Ovarian Reserve Markers

Abstract: Management of ovarian dysfunctions requires accurate estimation of ovarian reserve (OR). Therefore, reproductive hormones and antral follicle count (AFC) are assessed to indicate OR. Serum anti-Mullerian hormone (AMH) is a unique biomarker that has a critical role in folliculogenesis as well as steroidogenesis within ovaries. Secretion from preantral and early antral follicles renders AMH as the earliest marker to show OR decline. In this review we discuss the dynamics of circulating AMH that remarkably vary w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0
29

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 69 publications
6
62
0
29
Order By: Relevance
“…These include the requirement of latest equipment and skilled personnel, biasness due to operator’s variability, incapability to visualize follicles in female with ovarian cysts or prior surgery, and counting both healthy and atretic follicles as capable to respond to treatment. [14] Therefore, we compared the strength of FSH; mostly commonly used OR in secondary care clinics and AMH; recently acclaimed as the best solo marker to reflect ovarian pool, in segregating infertile population. As blood test has a clear advantage of sample collection and avoidance of human error, these tests may be easily used in setups lacking the sophisticated technology to assess AFC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the requirement of latest equipment and skilled personnel, biasness due to operator’s variability, incapability to visualize follicles in female with ovarian cysts or prior surgery, and counting both healthy and atretic follicles as capable to respond to treatment. [14] Therefore, we compared the strength of FSH; mostly commonly used OR in secondary care clinics and AMH; recently acclaimed as the best solo marker to reflect ovarian pool, in segregating infertile population. As blood test has a clear advantage of sample collection and avoidance of human error, these tests may be easily used in setups lacking the sophisticated technology to assess AFC.…”
Section: Discussionmentioning
confidence: 99%
“…As blood test has a clear advantage of sample collection and avoidance of human error, these tests may be easily used in setups lacking the sophisticated technology to assess AFC. [14]…”
Section: Discussionmentioning
confidence: 99%
“…A similar decline in AMH levels has also been seen in women where they even become undetectable after the menopause (La Marca et al., ). In women aged between 25 and 40 years, AMH levels of 1.0–3.0 μg/L are classified as normal, between 0.7 and 0.9 μg/L as low normal, from 0.3 to 0.6 μg/L as low and <0.3 μg/L are considered to be very low (Jamil, Fatima, Ahmed, & Malik, ). It has not yet been investigated whether queens also experience such a decline where AMH becomes undetectable after a certain age.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies decrease of AMH concentration has been observed as a result of oncological chemotherapy [19,[22][23][24]. Additionally, lower serum AMH concentrations are linked to obesity [25]. In women with CKD the aforementioned fertility disturbances may be caused by the damage of the ovaries by uremia, but no studies concerning the serum AMH concentration in women with CKD have been conducted so far.…”
Section: Introductionmentioning
confidence: 99%